Rhodium‐Catalyzed PIII‐Directed ortho‐C−H Borylation of Arylphosphines. Issue 7 (25th January 2019) - Wen, Jian; Wang, Dingyi; Qian, Jiasheng; Wang, Di; Zhu, Chendan; Zhao, Yue; Shi, Zhuangzhi
Abstract: Transition‐metal‐mediated metalation of an aromatic C−H bond that is adjacent to a tertiary phosphine group in arylphosphines via a four‐membered chelate ring was first discovered in 1968. Herein, we overcome a long‐standing problem with the ortho ‐C−H activation of arylphosphines in a catalytic fashion. In particular, we developed a rhodium‐catalyzed ortho ‐selective C−H borylation of various commercially available arylphosphines with B2 pin2 through P III ‐chelation‐assisted C−H activation. This discovery is suggestive of a generic platform that could enable the late‐stage modification of readily accessible arylphosphines. Abstract : More than a ligand : A rhodium catalytic system has been established for the direct and ortho ‐selective borylation of commercially available arylphosphines by P III ‐directed C−H activation. A series of ortho ‐boronated phosphines with different steric and electronic properties were obtained in high yields.